The pandemic-related factors associated with emergency department visits in Portugal throughout two years of the pandemic - Kinaan, Walaa (2023)
Funding Information: The present publication was funded by Fundação Ciência e Tecnologia, with IP national support through CHRC (UIDP/04923/2020). Publisher Copyright: © 2023 by the authors.